QASAM VERSES IN JUZ 'AMMA OF THE QUR' AN WITH IBNU 'ASYUR PERSPECTIVE - Ummil Mudawiyah (Dirosatuna: Journal of Islamic Studies, 2022)
This study examines the meaning of the Qasam verses in al-Qur'an (pledges in the Qur'an) contained in juz 30 in the view of Ibn 'A<syu>r in the book of Tafsir al-Tah}ri>r wa al-Tanwi>r. This research aims to provide new knowledge regarding the meaning of the pledges verses in the Qur’an. The existence of Allah's pledge in the Qur'an, moreover an pledge in the names of His creatures, is an attraction to find out the secrets implied in this pledge verse. Furthermore, linguistic analysis is needed to find out the meaning. This study uses the Tafsir al-Tah}ri>r wa al-Tanwi>r as an analysis approach. This research uses a qualitative method with the type of research library research, which takes sources from the literature in the form of books, books, journals, and previous scientific research that discusses the Qasam verses in al-Qur'an and the book of Tafsir al-Tah}ri>r wa al-Tanwi>r with descriptive analysis techniques. The results of this study indicate that Ibn 'A<syu>r explains the Qasam verses in juz 30 with a comprehensive explanation. They started by explaining the purpose of the Qasam verses, the meaning of each Muqsam bih (object of the pledge), and the relevance between Muqsam bih and Muqsam 'alaih (information reinforced by a pledge), and the context of the revelation of the verses.